Does Financial Development Induce Economic Growth in UAE? The Role of Capitalization and Foreign Direct Investment - Sbia, Rashid; Alrousan, Sahel (International Journal of Economics and Financial Issues, 2016)
This paper examines the association between financial progress and economic growth in the United Arab Emirates over the period 1975Q1-2012Q4. We have employed Bayer-Hanck (2013) combined non-cointegration to test the long run relationship. Our analysis revealed the existence of cointegration between financial development and economic growth. It also revealed that capitalization and FDI stimulate economic growth. The findings suggest that proper use of FDI and financial policy redesign will sustain economic growth in long term. Keywords: Financial Development, FDI, Capital investment, Growth, UAE. JEL Classifications: E22, C32, F43, G18, G28